EFFECTS OF WASHING TREATMENT ON THE CHARACTERISTICS OF ROADSIDE FRESH FRUITS - Julfi Restu Amelia; N. Ambarsari; Giyatmi Giyatmi (Food ScienTech Journal, 2021)
Roadside fruits are very possible to be contaminated by heavy metals and microbial contamination, especially fruits that are usually consumed unpeeled, such as grapes, water guava, apples, and starfruit.  Heavy metal contaminants that are hazardous to health include lead (Pd), cadmium (Cd), and arsenic (As), while harmful microbial contaminants include Escherichia coli and Salmonella thypii. This study aims to determine the effect of washing treatment on the characteristics (heavy metal and microbial contamination) of some fresh fruit. Washing process using running water and food grade soap. The design of the study used is Randomized Block Design, if it had a significant effect, it was further tested using the Duncan Multiple Range Test (DMRT).  The results of study showed that washing with food grade soap is preferable, as it shows a significant reduction in the levels of heavy metal and microbiological contents up to 0.000 mg / kg for Pb and Cd; 0.041 mg / kg for As; 0 kol / g for E. coli and 0 kol / 25g for Salmonella thypii.